Penggunaan Media Flashcard Bergambar Dalam Menanamkan Nilai Agama dan Moral Anak Usia Dini - Mauliza Nabila; Khadijah Khadijah; Prima Suci Rohmadheny (Universitas Islam Negeri Sumatera Utara, 2026)
Early childhood education plays an important role in developing children’s religious and moral values; however, monotonous teaching methods often make children less interested in participating in the learning process. This study aims to describe the use of pictorial flashcard media in instilling religious and moral values in early childhood at RA Raudatul Ilmi Medan. This research employed a descriptive qualitative approach involving teachers, the school principal, and children aged 5–6 years as the research subjects. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings showed that the use of pictorial flashcards helped children better understand positive behaviors such as greeting others, being honest, sharing with friends, and respecting teachers. Children also appeared more active, enthusiastic, and responsive during the learning process. Therefore, the consistent use of engaging visual media is recommended to support the development of religious and moral values in early childhood.